The use of blue-light cystoscopy in the detection and surveillance of nonmuscle invasive bladder cancer - Ellen M. Cahill; Kevin Chua; Sai Krishnaraya Doppalapudi; Saum Ghodoussipour (Current Urology, 2022)
Abstract. Nonmuscle invasive bladder cancer is associated with a high risk of recurrence as well as progression to muscle-invasive disease. Therefore, adequate visualization and identification of malignant lesions as well as complete resection are critical. Traditional white-light cystoscopy is limited in its ability to detect bladder cancer, specifically carcinoma in situ. Blue-light cystoscopy makes use of the intravesical instillation of a heme precursor to differentiate areas of malignancy from normal tissue. A narrative review of the literature on the use of blue-light cystoscopy in bladder cancer was conducted. Blue-light cystoscopy has been shown in several randomized clinical trials to increase detection of Ta, T1, and carcinoma in situ, as well as reduce risk of recurrence at 12 months as compared with traditional white-light cystoscopy. Research into the effects of blue-light cystoscopy on risk of disease progression has produced mixed results, in part due to changing definitions of progression. However, more recent research suggests a correlation with decreased risk of progression. Whereas the use of blue-light was initially limited to rigid cystoscopy in the operating room, results from a recent randomized clinical trial showing enhanced detection of recurrent disease using blue-light in-office surveillance flexible cystoscopy have led to expanded Food and Drug Administration approval. Overall, blue-light cystoscopy offers promise as an enhancement to white-light cystoscopy for the detection of nonmuscle invasive bladder cancer and may yield additional benefits in reducing disease recurrence and progression. Further prospective research is needed to evaluate the true benefit of blue-light cystoscopy in terms of disease progression as well as the cost-effectiveness of this technique.